Preparation and Characterization of Cyano Complexes of Oxotungsten(IV) with Mannich Base Ligands - Mohita Sharma; Mohd Saleem; Balgar Singh; H. N. Sheikh; B. L. Kalsotra (E-Journal of Chemistry)
Oxocyanotungsten(IV) complexes, (Ph3P)2 NH2 [WO(CN)3 L–L]. 3H2O and Cs[WO(CN)3L–L].H2O (where L–L = morpholinobenzyl benzamide (MBB), piperidinobenzyl benzamide (PBB), piperidinobenzyl urea (PBU), piperidinobenzyl thiourea (PBTU), morpholinobenzyl urea (MBU) and morpholinobenzyl thiourea (MBTU)) were synthesized. The complexes have been prepared by the reaction of K3Na [WO2(CN)4].6H2O with morpholinobenzyl urea and related ligands in aqueous solution around pH of 7-8. These have been isolated as bis(triphenylphosphine)iminium or cesium salts. The complexes have been characterized by elemental analysis, IR, 1H NMR, UV-Vis spectra, magnetic susceptibility, conductivity measurements and TGA/DTA studies.